MicroRNA‐181a is involved in insulin‐like growth factor‐1‐mediated regulation of the transcription factor CREB1. (6th August 2013) - Liu, Yang; Zhao, Zhao; Yang, Fan; Gao, Yimei; Song, Jian; Wan, Yu
Abstract microRNAs are a class of small non‐coding RNA molecules negatively regulating gene expression at post‐transcriptional level in many tissues including the central nervous system. cAMP response element binding protein (CREB) is a key nuclear factor highly expressed in hippocampal neurons on which many signal pathways converge. Recent studies have found that microRNA‐181a is rich in mature nerve cells, and bioinformatics analysis shows that the CREB1 mRNA 3′‐untranslated region (3′UTR) contains complementary sequence to the miR‐181a seed region. In this study, we investigated whether miR‐181a is a negative regulator for CREB1 expression in neurons. It was found that the expression of miR‐181a was negatively correlated with Insulin‐like growth factor‐1 (IGF‐1) and CREB1 in the Lewis rat hippocampus. miR‐181a bound to CREB1 mRNA through a specific binding site in the 3′UTR sequence. The expression of CREB1 in PC12 cells was down‐regulated by transfection with a miR‐181a mimic and up‐regulated by a miR‐181a inhibitor. A down‐regulated miR‐181a and an up‐regulated CREB1 were observed in IGF‐1‐stimulated PC12 cells. And miR‐181a inhibited dendritic growth of cultured hippocampus neurons. These suggest that miR‐181a is involved in IGF‐1‐regulated CREB1 expression by targeting its mRNA 3′UTR. <boxed-text content-type="graphic" id="jnc12370-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> microRNAs (miRNAs) regulate gene expression at the post‐transcriptional level and are involved in the central nervous system development. Here, we demonstrate that miR‐181a can inhibit the expression of the transcription factor CREB1 by specifically targeting its mRNA 3′UTR and inhibit the development of hippocampus neurons. Repressed expression of miR‐181a is involved in IGF‐1‐mediated up‐regulation of CREB1 in vivo and in vitro. These findings indicate that miR‐181a could be a potential target for preventing neurodegenerative diseases.